A Plate‐Mantle Convection System in the West Pacific Revealed by Tertiary Ultramafic‐Mafic Volcanic Rocks in Southeast China. Issue 11 (5th November 2021) - Pan, Fa‐Bin; Jin, Chong; He, Xiaobo; Tao, Lu; Jia, Bao‐Jian
Abstract: Cenozoic volcanic rocks in the East Asian continental margin usually form because of asthenosphere upwelling and resultant decompression melting, and their origins are important in deciphering mantle geodynamics attributed to intraplate volcanism. In this study, Oligocene basanite‐tephrite rocks were found in continental interior outcrops, and Miocene to Pliocene basanite, alkaline basalt, and olivine tholeiite were abundant in coastal areas in Zhejiang, Southeast China. Episodic magmatic activities appeared to migrate oceanward with an ∼100‐km spatial gap, which was temporally and spatially synchronized with repeated retreat and rollback of the Tertiary westward subducting Pacific slab. All rocks had OIB‐like trace‐element patterns, but the basanite‐tephrite rocks contained higher LILE, HFSE, and LREE than the alkaline basalt and olivine tholeiite. Geochemical modeling indicated the basanite‐tephrite and the alkaline and olivine tholeiite basalts had low‐degree (7%–15%) and slightly higher degree (20%–30%) partial melting of heterogeneous pyroxenite sources, respectively. In addition, their magma sources showed a progressive weakening of carbonatite metasomatism and decreasing melting depths. Those features were tightly associated with punctuated upwelling of asthenospheric materials, most likely metasomatized by the stagnant Pacific slab‐derived silica/carbonatite melts. A plate‐mantle convection system is proposed in which asthenosphere materials pulled by the subducting Pacific slab explain the intraplate volcanism in East Asia as asthenospheric upwelling, which formed by escaping from either slab tears or slab front edges in the mantle transition zone. Plain Language Summary: Oligocene basanite‐tephrite rocks were found in the continental interior, whereas Miocene to Pliocene basanite, alkaline basalt, and olivine tholeiite were abundant in coastal areas in Zhejiang, Southeast China. Episodic magmatic activities appeared to migrate oceanward with ∼100‐km spatial gap, which was temporally and spatially synchronized with repeated retreat and rollback of the Tertiary westward subducting Pacific slab. A plate‐mantle convection system indicates that asthenosphere materials pulled by the subducting Pacific slab can explain the intraplate volcanism in East Asia as the asthenospheric upwelling, which formed by escaping from either slab tears or slab front edges in the mantle transition zone. Key Points: Oligocene‐Pliocene magmatic activities appeared to migrate oceanward with a ∼100‐km spatial gap Spatial‐temporal synchronization occurred with repeated retreat and rollback of the subducting Pacific slab A plate‐mantle convection system is proposed for the West Pacific and East Asia